Operator 4.0 or Maker 1.0? Exploring the implications of Industrie 4.0 for innovation, safety and quality of work in small economies and enterprises. (January 2020) - Taylor, Mark P.; Boxall, Peter; Chen, John J.J.; Xu, Xun; Liew, Angela; Adeniji, Adebayo
Highlights: Unleash human creative potential to complement the robotic and virtual world of Advanced Manufacturing. Factory Operators transitioning to the role of a "Maker" and working alongside automated production systems. Argues for the design of work organization models that ensure an enhanced role for humans. Considers safety and productivity issues under Industry 4.0. Abstract: Many authors have advocated a human–centric view of Industrie 4.0 automation, in which the human operator works with augmented powers and capabilities such as super-strength, artificial intelligence and virtual reality, although their roles are still in the manufacture of the product. A human-automation symbiosis in the production process, with robotic and IOT tools helping to extend and meld the capabilities of the Operator to accomplish the tasks of production is a proposed goal. The approach taken in the present work does not, however, envisage a super-human outcome. Rather, the goal is the unleashing of human creative potential, as a complement to the robotic and virtual world of the automated production system. Agile manufacturers typically run small scale operations (20 people or less), make short runs of many products and are continuously involved in their design – both at detailed and conceptual levels. This can be a strength in terms of international competitiveness where knowledge of the production process, the product end user needs, and the machinery and tooling itself combine to produce innovation. SME manufacturers are actually designers. Their employees think about design as they manufacture. We foresee that the Operator may transition to a Maker – a person who works alongside the automated production system but with a different role - one which is essentially creative, rather than assisting or monitoring non-discretionary work flow steps or processes.